The Analysis of Violation Maxim to Create Adult Humor in Amphibia Animated TV Series (2019) - Reforman, Muhammad Gagah; Fitrawati, Fitrawati (English Language and Literature, 2024)
In the US animation industry, there is an increasing trend of incorporating adult humor into children's entertainment. This research investigates how adult humor is created by violating Grice's cooperative principles (maxims) in Amphibia animated series. The research is analyzed by identifying the type of violating maxim and how each violated maxim co-occurs with rhetorical techniques using Grice's cooperative principle theory (1975) with Tupan and Natalia's violating maxim criteria (2008) and Berger's humor techniques (1993, 1997). This research found that violating the maxim of quality is the most common way to make adult humor at 28.26%, followed by violating the maxim of manner at 15.22% and relation at 10.87%. However, other types of maxim violations were below 10%. The dominant type of rhetorical technique used in Amphibia involves irony/sarcasm, with 28.26%. Exaggeration is the second most common type, with 19.57%. While absurdity and ridicule each with 17.39%. Nevertheless, the rest of the rhetorical techniques were below 10%. These findings conclude that violating the maxim can lead to indirectness and leads to unconventional methods of communication. Adults tend to understand this better than children, who often take things literally. Additionally, the characters in Amphibia violate multiple maxims simultaneously, possibly to appeal to an adult audience. The show also uses difficult rhetorical techniques for children to grasp, such as irony/sarcasm, exaggeration, absurdity, and ridicule.